Pro Ajax and Java Frameworks - Schutta, Nathaniel. (Apress : Imprint: Apress, 2006)
As a Java developer, you want a guide that shows you how to add Ajax functionality to your web applications with a minimum of effort. Look no further than Pro Ajax and Java Frameworks! In this book, recognized Java experts and authors of the bestselling Apress title Foundations of Ajax will show you how. The authors begin by recapping Ajax basics. Then they unveil a comprehensive Java/Ajax toolkit. Tools include JSEclipse for code editing, Venkman for JavaScript debugging, and Dojo Compressor for code compression. They also explain Log4js (and other tools) for JavaScript logging, JsUnit (and others) for testing, and various libraries like AjaxTags, DWR, and Script.aculo.us for rapid code development. The last part of the book shows you how to build up a series of professional Java/Ajax applications. These will incorporate some of today's most popular frameworksSpring, JSF, Struts, and Tapestry, giving you all you need to incorporate Ajax into your everyday work and become an Ajax expert!